2008
DOI: 10.1097/ico.0b013e318166c40c
|View full text |Cite
|
Sign up to set email alerts
|

Combined Wedge Resection and Beveled Penetrating Relaxing Incisions for the Treatment of Pellucid Marginal Corneal Degeneration

Abstract: Corneal wedge resection combined with paired, opposed clear corneal penetrating relaxing incisions is a suitable surgical option for the treatment of PMCD, providing early adequate astigmatic control with long-term stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…4 Instead, wedge resection offers the advantage of removing the ectatic tissue and preserving the recipient cornea, restructured in a shape compatible with useful vision in the vast majority of cases. 5 However, to be able to perform wedge resections, the lips of the resulting wound must be thick enough to allow safe suturing to be done. In extremely advanced cases such as those of our small series, excision of the entire ectasia up to tissue thick enough for suturing would have reached too far both centrally and peripherally, making it impossible to close the wound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Instead, wedge resection offers the advantage of removing the ectatic tissue and preserving the recipient cornea, restructured in a shape compatible with useful vision in the vast majority of cases. 5 However, to be able to perform wedge resections, the lips of the resulting wound must be thick enough to allow safe suturing to be done. In extremely advanced cases such as those of our small series, excision of the entire ectasia up to tissue thick enough for suturing would have reached too far both centrally and peripherally, making it impossible to close the wound.…”
Section: Discussionmentioning
confidence: 99%
“…1 Visual rehabilitation in advanced stages can be achieved only by the surgical treatment of the irregular high-degree astigmatism: intracorneal ring segments, thermokeratoplasty, crescentic lamellar or full-thickness resection, large central or eccentric keratoplasty of both the lamellar (LK) and the penetrating type, crescentic LK, and epikeratophakia have all been performed giving different results. [2][3][4][5] However, when extreme thinning affects a wide area of the peripheral cornea and extends to most of its circumference, the above-mentioned procedures may be technically difficult to perform and may result in poor visual outcomes.…”
mentioning
confidence: 99%
“…Casos moderados e graves são tratados com cirurgias tais como ressecção em crescente, ressecção lamelar em crescente, ceratoplastia lamelar, ceratoplastia penetrante, epiceratoplastia, uso de segmentos intraestromais corneais de PMMA, incisões relaxantes limbares e implante de lentes fácicas (1,(4)(5)(6)(7)(8)(9) . A variedade de opções cirúrgicas demonstra a ausência de um tratamento plenamente eficaz para DMP.…”
Section: Discussionunclassified
“…Maccheron and Daya54 have reported wedge resection followed by complete (limbus to limbus) or partial host deep lamellar dissection to enable closure by mobilising the host anterior lamellar cornea for cases of PMD. Busin et al 55 have reported corneal wedge resection combined with paired, opposed clear corneal penetrating relaxing incisions for the treatment of PMD. After crescent-shaped wedge excision of the thinned area inferiorly, the anterior chamber is filled with viscoelastic, and a 3.2-mm metal keratome is used to create two bevelled, penetrating, clear-corneal keratotomies, one at each of the topographic steep axes, immediately anterior to the limbus.…”
Section: Managementmentioning
confidence: 99%